PENERAPAN STANDAR AKUNTANSI KEUANGAN ENTITAS TANPA AKUNTABILITAS PUBLIK (SAK ETAP) PADA KOPERASI MELATI POLRES SINGKAWANG - B1035131031, Bagus Maulana (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2016)
The aim of this research was to find out the implementation of the Indonesian Financial Accounting Standar for Non Publicly Accountable Entitas (SAK ETAP) in preparing the financial statements at the Melati Cooperative of Singkawang Municipal Police. This study used was a qualitative method which was conducted in three stages i.e. (1) data collection, (2) data display, and (3) data analysis and concluion. The researcher analyzed the data by inventorying financial statement presented by the Melati Cooperative of Singkawang Municipal Police in order to draw conclusions. The research findings based on the analysis of financial statement of the Melati Cooperative of Singkawang Municipal Police indicated that the Cooperative had not fully applied the Indonesian Financial Accounting Standards for Non Publicly Accountable Entities (SAK ETAP) as a guide in preparing its financial statements. Keywords: Cooperative, Financial Statement, SAK ETAP